HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN PRESTASI BELAJAR SISWA KELAS IV SD DI SDN 056627 KWALA SAWIT - Mei Manullang; Syahrial; Zainuddin; Lala Jelita Ananda; Nur Hudayah Manjani (STKIP Subang, 2026)
This study aimed to determine the relationship between parenting styles and the learning achievement of fourth grade students at SDN 056627 Kwala Sawit in the 2025/2026 academic year. This study used a quantitative method with a correlational approach. The population consisted of all fourth grade students at SDN 056627 Kwala Sawit, with a sample of 24 students selected using the total sampling technique. The research instruments included a parenting style questionnaire using the Guttman scale, interviews, and documentation of students’ scores to measure learning achievement. The instruments were tested for validity and reliability before being used. The data analysis techniques included descriptive statistical analysis and Product Moment correlation analysis. The results showed that the correlation coefficient (r calculated) was 0.727, which is categorized as strong, with a significance value of 0.00 < 0.05. The hypothesis test results indicated that r calculated (0.727) was greater than r table (0.404), so the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. This indicates that there is a significant relationship between parenting styles and students’ learning achievement. The conclusion of this study is that there is a significant and strong relationship between parenting styles and the learning achievement of fourth grade students at SDN 056627 Kwala Sawit. The better the parenting style, the higher the students’ learning achievement.